Vzaimoobuslovlennost' obscej fiziceskoj rabotosposobnosti i tipov energoobespecenija mysecnoj dejatel'nosti legkoatletov -sprinterov i stajerov - Lazareva, E. A. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of this paper was the correlation of the general physical serviceability and the type of energy support of muscular activity in sprinters and long-distance runners. The reference of tested athletes to the certain type energy support was carried out with the help of cycling energy test, and definition of the general physical serviceability - by the definition of the maximal consumption of oxygen. During the carried out cycling energy testings it was revealed, that in sprinters the dominant type of energy support is anaerobic. This type is determining the greatest serviceability in the zone of the maximal power. The aerobic type of energy support appeared in long-distance runners, that determines their greatest serviceability in the zone of moderate and high-power.